Adapter proteins SLP-76 and BLNK both are expressed by murine macrophages and are linked to signaling via Fcγ receptors I and II/III - Bonilla, Francisco A. (The National Academy of Sciences, 2000)
The SLP-76 (Src homology 2 domain-containing leukocyte protein of 76 kDa) adapter protein is expressed in T cells and myeloid cells, whereas its homologue BLNK (B cell linker protein) is expressed in B cells. SLP-76 and BLNK link immunoreceptor tyrosine-based activation motif-containing receptors to signaling molecules that include phospholipase C-γ, mitogen-activated protein kinases, and the GTPases Ras and Rho. SLP-76 plays a critical role in T cell receptor, FcɛRI and gpVI collagen receptor signaling, and participates in signaling via FcγR and killer cell inhibitory receptors. BLNK plays a critical role in B cell receptor signaling. We show that murine bone marrow-derived macrophages express both SLP-76 and BLNK. Selective ligation of FcγRI and FcγRII/III resulted in tyrosine phosphorylation of both SLP-76 and BLNK. SLP-76(−/−) bone marrow-derived macrophages display FcγR-mediated tyrosine phosphorylation of Syk, phospholipase C-γ2, and extracellular signal regulated kinases 1 and 2, and normal FcγR-dependent phagocytosis. These data suggest that both SLP-76 and BLNK are coupled to FcγR signaling in murine macrophages.